2021
DOI: 10.1177/00224871211015980
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Responding Component of Teacher Noticing: A Case of One Teacher’s Pedagogical Responses to Students’ Thinking in Classroom Artifacts

Abstract: In this study, we investigated how an experienced fourth-grade teacher responded to her students’ thinking as part of her teacher noticing practice in a formative assessment context. Our primary purpose in doing this work was to decompose the responding component of teacher noticing and use our findings to present an emerging framework characterizing the multidimensional nature of this practice. We present two key outcomes based on the findings of this work. First, we show how a formative assessment context si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…At the same time, prior research has highlighted the importance of promoting deep dialogue about the relationship between student thinking, racialized classroom phenomena, and teachers’ instructional moves (e.g., Horn & Little, 2010; Shah & Coles, 2020). Offering a suggestion right away might short-circuit this process (Segal et al, 2018), or alternatively support the development of strong pedagogical responses to teachers’ noticings (Luna & Selmer, 2021). Future research might delve more deeply into the nature of such suggestions, examining their relationship to ongoing productive discourse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, prior research has highlighted the importance of promoting deep dialogue about the relationship between student thinking, racialized classroom phenomena, and teachers’ instructional moves (e.g., Horn & Little, 2010; Shah & Coles, 2020). Offering a suggestion right away might short-circuit this process (Segal et al, 2018), or alternatively support the development of strong pedagogical responses to teachers’ noticings (Luna & Selmer, 2021). Future research might delve more deeply into the nature of such suggestions, examining their relationship to ongoing productive discourse.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have found that evaluations or judgments of teachers’ actions sometimes take precedence in conversation (Borko et al, 2008; Sherin & van Es, 2009). Thus, fostering discourse that centers on noticing and interpreting student thinking and racialized classroom phenomena, as well as supporting teachers in responding effectively to what they notice (Luna & Selmer, 2021), is another important challenge in professional learning settings.…”
Section: Conceptual Groundingmentioning
confidence: 99%
“…Several studies note how degrees of sophistication in the use of noticing skills contribute to differential uptake of reform practices, and suggest that noticing skills may play an important role in teacher change (Barnhart & van F I G U R E 2 Number of interview excerpts for domain of consequence subcodes by teacher change category. Es, 2015;Jacobs et al, 2010;Luna & Selmer, 2021;Sherin, 2002). For example, Franke et al's (2001) study of differential uptake of reform practices among 22 teachers in one school district found that teachers who engaged in their own sensemaking around students' learning processes-characteristics they described as "generative change (p. 653)"-were more likely to integrate students' learning strategies into instructional practice than teachers not attending as closely to student learning.…”
Section: The Role Of Noticing Student Learning In Teacher Changementioning
confidence: 99%
“…We turn to research on teacher noticing to frame teachers' attention and sensemaking of student thinking for enacting responsive teaching. Across the literature is a wide consensus that core to responsive teaching is teachers' ongoing attention and sensemaking of student thinking and using their evolving understanding of students' thinking to move students' learning forward (Barnhart & van Es, 2015, Blömeke et al, 2015; Jacobs et al, 2010; Luna, 2018; Luna & Selmer, 2021; Richards & Robertson, 2016; Tekkumru‐Kisa et al, 2022; Sherin & van Es, 2009; Thomas et al, 2021; van Es & Sherin, 2021). More recent research refines and expands the fields' understanding of noticing for responsive teaching.…”
Section: Theoretical Frameworkmentioning
confidence: 99%